The Autophagy Receptor TAX1BP1 (T6BP) improves antigen presentation by MHC‐II molecules. (10th October 2022) - Sarango, Gabriela; Richetta, Clémence; Pereira, Mathias; Kumari, Anita; Ghosh, Michael; Bertrand, Lisa; Pionneau, Cédric; Le Gall, Morgane; Grégoire, Sylvie; Jeger‐Madiot, Raphaël; Rosoy, Elina; Subra, Frédéric; et al.
Abstract: CD4 + T lymphocytes play a major role in the establishment and maintenance of immunity. They are activated by antigenic peptides derived from extracellular or newly synthesized (endogenous) proteins presented by the MHC‐II molecules. The pathways leading to endogenous MHC‐II presentation remain poorly characterized. We demonstrate here that the autophagy receptor, T6BP, influences both autophagy‐dependent and ‐independent endogenous presentation of HIV‐ and HCMV‐derived peptides. By studying the immunopeptidome of MHC‐II molecules, we show that T6BP affects both the quantity and quality of peptides presented. T6BP silencing induces the mislocalization of the MHC‐II‐loading compartments and rapid degradation of the invariant chain (CD74) without altering the expression and internalization kinetics of MHC‐II molecules. Defining the interactome of T6BP, we identify calnexin as a T6BP partner. We show that the calnexin cytosolic tail is required for this interaction. Remarkably, calnexin silencing replicates the functional consequences of T6BP silencing: decreased CD4 + T cell activation and exacerbated CD74 degradation. Altogether, we unravel T6BP as a key player of the MHC‐II‐restricted endogenous presentation pathway, and we propose one potential mechanism of action. Synopsis: The autophagy receptor T6BP (TAX1BP1) stabilizes the invariant chain (CD74) and regulates MHC‐II trafficking, thereby favoring the presentation of high‐affinity peptides to virus‐specific CD4 + T cells. T6BP loss prevents the activation of HIV‐ and HCMV‐specific CD4 + T cell clones. T6BP expression affects the quality and the diversity of peptides presented by MHC‐II molecules. T6BP interacts with the cytoplasmic tail of calnexin to favor MHC‐II molecule chaperoning by the invariant chain (CD74). Calnexin loss replicates T6BP silencing: decreased CD4 + T cell activation and exacerbated CD74 degradation. Abstract : The autophagy receptor T6BP (TAX1BP1) stabilises the invariant chain (CD74) and regulates MHC‐II trafficking, thereby favouring the presentation of high affinity peptides to virus‐specific CD4 + T cells.